Community champions of ecosystem services: The role of local agency in protecting Indonesian coral reefs - Abdurrahim, Ali Yansyah; Adhuri, Dedi Supriadi; Ross, Helen; Phelan, Anna (Frontiers in Ecology and Evolution, 2022)
The importance of communities is well recognised in the protection and enhancement of ecosystem services, yet the influences of individuals within and on communities are often overlooked. Individual and community agency are pertinent in small-scale fisheries, given that livelihoods of many millions of these fishers worldwide depend on ecosystem services derived from coral reefs and seagrass beds. In eastern Indonesia the rapid spread of destructive fishing practices has serious impacts on these marine and coastal ecosystems. Policy is complex, with three levels of government involved, and communities also seeking to apply customary marine management and fishing rules. Effective deterrence and enforcement prove difficult for both communities and government, especially in remote places. Community-based marine protected areas, and government or aid-led educational programs, are attempted, but are insufficient against the pressures of well-organized illegal fishing supply chains. On Selayar Island, in South Sulawesi province, Indonesia, certain local “champions”, fishers and others exerting influence within their communities, and “island champions”, individuals working at island level from local government and non-government roles, are developing their own – often unorthodox - strategies to mobilize social change to protect ecosystem services. Through in-depth interviews supported by participant observation we investigated how these individuals become motivated, and how they operate to protect local ecosystems such as coral reefs and seagrass meadows. We document what inspired them, what strategies they follow, their observations on barriers, and their key messages for others. Understanding these very unofficial, individual and small-group processes that occur outside conventional policy-making and ecosystem governance can allow sharing of effective strategies to encourage potential champions elsewhere, and support community agency in protecting marine ecosystem services.